Методи та засоби підвищення ефективності обслуговування запитів в інформаційній мережі - Турута, О. П. (My University, 2011)
Дисертація присвячена вирішенню актуальної задачі підвищення ефективності обслуговування запитів в інформаційній мережі на основі розроблених методів оцінки корисності обслуговування запитів, визначення пріоритету обслуговування та забезпечення доступності ресурсів. В роботі розроблена агентно-орієнтована модель інформаційної мережі, обґрунтовані оцінки корисності обслуговування запиту в інформаційній мережі та доступності сервісу. На підставі розроблених оцінок були запропоновані метод визначення пріоритету обслуговування запиту та метод забезпечення доступності ресурсів сервісу інформаційної мережі. Для отримання більш точної характеристики клієнта була вдосконалена методика ідентифікації агента. На основі розроблених методів запропонована інформаційна технологія підвищення ефективності обслуговування запитів в інформаційній мережі. The thesis is devoted to solving the actual problem of increasing the efficiency of requests service in network. Devoted method is based on estimation of utility service requests, setting priorities for service and access to resources. Information technology is developed on devoted methods. Information technology increase the efficiency of service requests in an information network. We consider the process of service requests in an information network under high network load. To solve this problem were considered models of existing networks and methods to ensure quality of service requests. Existing models do not take into account the self-similar traffic characteristics and methods of traffic control is underutilized information about traffic. To solve this problem was developed agent-based model of information networks. Based on estimates developed methods were developed for the priority service request and method for providing access to resources, service information network. To obtain more precise characteristics of the client has been improved method of identification of the agent. Based on the proposed assessments and methods been implemented information technology improve the quality of service requests in an information network. The developed technology consists of six stages, which use the developed methods, estimates and methodology.
Keywords: інформаційна мережа; мережа передачі даних; клієнт; агентно-орієнтована модель мережі; якість обслуговування; критерії якості обслуговування; доступність сервісу; фрактальний телекомунікаційний трафік; моделювання трафіку; information network; networks of telecommunications; client; service; agent-oriented model of network; quality of service; criteria’s quality of service; fractal telecommunication traffic; traffic modeling